Factors Affecting Job Satisfaction of Faculty Members - Võ, Văn Việt (H. : ĐHQGHN, 2017)
The purpose of this study is to determine the overall level of job satisfaction, and to examine factors affecting job satisfaction of faculty members at University of Agriculture and Forestry Ho Chi Minh City (UAF). A descriptive-correlational survey research design was applied to answer the research questions and test the study hypotheses. Frequencies, percentages and appropriate summary statistics were computed for the demographic characteristics, factors of job satisfaction. Correlation coefficients were calculated to assess relationships between the selected characteristics. The descriptive analysis of the data indicates that the mean for the overall level of job satisfaction is 3.97 with a standard deviation of .909. The median and mode score is four. This is indicative of an above average level of satisfaction; it appears as though the majority of the employees in the sample are satisfied with the nature of their job. A stepwise multiple linear regression was performed to determine the best predictor of the dependent variable - overall job satisfaction. The result showed that our independent variables (fiscal resources, personal growth and satisfaction, policy and administration) have accounted for 59% of the variance in the overall job satisfaction of faculty member.